DEVELOPMENT STRATEGY OF SUBAK BULUH AS AN AGRO-TOURISM DESTINATION IN BATURITI VILLAGE, KERAMBITAN DISTRICT, TABANAN REGENCY - Ida Bagus Putu Suryawan; Putu Fajar Kartika Lestari; Ni Gst. Ag.Gde Eka Martiningsih (Fakultas Pertanian dan Bisnis Universitas Mahasaraswati Denpasar, 2025)
This study aims to formulate development strategies for Subak Buluh as an agro-tourism destination in Baturiti Village, Kerambitan District, Tabanan Regency. Subak, as a traditional Balinese irrigation institution with strong socio-cultural values, plays a vital role in water management and agricultural sustainability. In response to contemporary challenges, subak must be developed not only as an agricultural institution but also as an alternative tourism attraction. Data were collected using purposive sampling from 78 respondents, consisting of 39 internal respondents (farmers and subak members) and 39 external respondents (tourists and local residents). Respondents exhibited diverse characteristics in terms of education level and occupation. SWOT analysis was employed to identify internal strengths and weaknesses as well as external opportunities and threats in the development of Subak Buluh agro-tourism. The results indicate that Subak Buluh’s main strengths include its natural landscape, cultural traditions and ceremonies, and fertile agricultural land. However, limitations such as insufficient internal funding and limited promotional activities remain key challenges. Promising development opportunities arise from village tourism programs and the growing global trend toward alternative tourism, while threats include tourist congestion and infrastructure degradation. This study provides strategic recommendations to support the sustainable development of Subak Buluh as an agro-tourism destination, contributing to local community welfare while preserving environmental and cultural sustainability